2017
DOI: 10.5433/1679-0359.2017v38n4supl1p2505
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds in different acerola fruit cultivares

Abstract: The increased consumption of acerola in Brazil was triggered because it is considered as a functional food mainly for its high ascorbic acid content, but the fruit also has high nutritional value, high levels of phenolic compounds, total antioxidant activity, anthocyanins and carotenoids in its composition. The objective was to evaluate the chemical, physical-chemical and antioxidant activity of eight varieties of acerola tree. The acerolas used in the research were the harvest 2015, 8 varieties: BRS 235 -Apod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
3
12
0
1
Order By: Relevance
“…3, Table S.1). Similar high L values were observed by Brunini et al (2004) and Mariano-Nasser et al (2017), while the lower values were lower than those reported in the literature (Table S.3). Looking at the box plot, it can be seen that the L parameter of half of the phenotypes was over the median value, and the other half below, which is in agreement with data reported by Godoy et al ( 2008) (Fig.…”
Section: Morphological Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…3, Table S.1). Similar high L values were observed by Brunini et al (2004) and Mariano-Nasser et al (2017), while the lower values were lower than those reported in the literature (Table S.3). Looking at the box plot, it can be seen that the L parameter of half of the phenotypes was over the median value, and the other half below, which is in agreement with data reported by Godoy et al ( 2008) (Fig.…”
Section: Morphological Parameterssupporting
confidence: 89%
“…Color is expressed using the rectangular coordinate system L* a* b *, according to the Commission Internationale de E'clairage (CIE 1986), where L* = percentage of the luminosity values (0% = black and 100% = white), a* = red (+) or green (-) and b* = yellow (+) or blue (-) (McGuire 1992). Color measurements were carried out by measuring the color reading twice per fruit, in opposite regions, to avoid the in uence of sun exposure on the fruit (Viúda-Martos et al 2010;Adriano et al 2011;Mondragón-Cortez et al 2013;Mariano-Nasser et al 2017).…”
Section: Fruit Size Weight Color Parameters and Pulp Yieldmentioning
confidence: 99%
“…However, the main commercial interest of acerola comes from its high ascorbic acid or vitamin C content as varieties contain from 1,500 to 4,500 mg. 100g-¹, almost 100 times the concentrations found in citrus fruits (Moreira et al, 2009;Almeida et al, 2014). In addition to the considerable amount of vitamin C, acerola is also good source of phenolic and carotenoid compounds, associated with fruit color besides their antioxidant defense potential (Calgaro & Braga, 2012;Mariano-Nasser et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although their values were not significantly different (p ≤ 0.05) among the studied varieties ranged from 169.62 to 210.80 mg GAE/g of dw. These values are higher than those found in other studies (Mariano-Nasser et al, 2017;Oliveira et al, 2012). It is known that some factors including polarity of the solvent may influence the efficacy of the extraction of compounds, as combinations of ethanol and water, which are efficient in the extraction of polyphenols due to the polarity of these mixtures being similar to those of phenolic compounds which may have provided greater solubilization of the solute and consequently, a higher extraction of these compounds (Machado et al, 2015).…”
Section: Physiochemical and Phytochemical Characterizationmentioning
confidence: 57%
“…Higher pH relates to lower acidity, which is consistent with the values observed in these results. It is worth mentioning that the acerola pH remains stable even in different maturation stages when compared to other varieties grown in Brazil (Ribeiro et al, 2019;Carmo et al, 2018;Mariano-Nasser et al, 2017). In this study, the SS/TA ratio presented variation between the studied varieties, (Table 1) demonstrating that these varieties are recommended for technological applications such as usage as a gelling agent, which corroborates the suggestion of Assis et al (2001), who proposed that acerola fruits in the green ripening stage can be an important source of pectin for confectionery industries.…”
Section: Physiochemical and Phytochemical Characterizationmentioning
confidence: 99%